2009
DOI: 10.1016/j.molcel.2009.09.018
|View full text |Cite
|
Sign up to set email alerts
|

“Cotranscriptionality”: The Transcription Elongation Complex as a Nexus for Nuclear Transactions

Abstract: Much of the complex process of RNP biogenesis takes place at the gene, co-transcriptionally. The target for RNA binding and processing factors is therefore not a solitary RNA molecule, but a transcription elongation complex (TEC) comprising the growing nascent RNA and RNA polymerase traversing a chromatin template with associated passenger proteins. RNA maturation factors are not the only nuclear machines whose work is organized co-transcriptionally around the TEC scaffold. In addition DNA repair, covalent chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
347
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(364 citation statements)
references
References 135 publications
6
347
1
3
Order By: Relevance
“…It is suggested that different combinations of Ser2, Ser5 and Ser7 phosphorylations as well as proline isomerization constitute a 'CTD code' , which orchestrates transcription with pre-mRNA processing, histone modification and spliceosomal subunit arrangements [3][4][5][6]54 . The unexpected finding that P-TEFb is a Ser5 CTD kinase with a preference for Ser7 pre-phosphorylations to generate Ser5/Ser7 double-phosphorylation marks requires further structural and functional investigations on the multifaceted CTD phosphorylation patterns and their corresponding recognitions.…”
Section: Y S P T S P S Y S P T S P S Y S P T S P Smentioning
confidence: 99%
“…It is suggested that different combinations of Ser2, Ser5 and Ser7 phosphorylations as well as proline isomerization constitute a 'CTD code' , which orchestrates transcription with pre-mRNA processing, histone modification and spliceosomal subunit arrangements [3][4][5][6]54 . The unexpected finding that P-TEFb is a Ser5 CTD kinase with a preference for Ser7 pre-phosphorylations to generate Ser5/Ser7 double-phosphorylation marks requires further structural and functional investigations on the multifaceted CTD phosphorylation patterns and their corresponding recognitions.…”
Section: Y S P T S P S Y S P T S P S Y S P T S P Smentioning
confidence: 99%
“…5 The CTD mediates coupling of transcription with pre-mRNA processing [6][7][8][9][10] by acting as a "landing pad" for recruitment of RNA processing factors to the transcription site, 11 thus facilitating co-transcriptional pre-mRNA processing (For a review see refs. [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Transcription and splicing are coupled processes (9,10). Splicing occurs cotranscriptionally, and multiple lines of evidence indicate that transcription elongation and splicing influence each other.…”
mentioning
confidence: 99%